Missouri Career Education Exemplary Classroom Activities for Kindergarten - Bernhardt, Edna Erickson; Missouri State Dept. of Elementary and Secondary Education, Jefferson City. Div. of Career and Adult Education ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1980)
This Exemplary Activities Handbook for kindergarten is one of nine booklets that organize career education activities around subject matter areas. (There is one booklet each for grades K-6, one for grades 7-9, and one for grades 10-12.) The booklet is organized around these subject matter areas: Fine Arts, Guidance, Health and Physical Education, Language Arts, Mathematics, Science, and Social Studies. Each subject matter area is divided into four sections in which activities are arranged according to the four Missouri Career Education Delivery System learning areas: Self Knowledge; Life Roles, Settings, and Events; Life Planning; and Academic and Vocational Skills. Activities, correlated to four goals within each learning area, are briefly described, and necessary information, lists, forms, etc., are provided. Four appendixes provide complete lists of teaching points for the goals in each learning area. (YLB)
ERIC Note: For related documents see CE 032 849-856.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Basic Skills; Career Education; Career Exploration; Class Activities; Communication (Thought Transfer); Decision Making; Fine Arts; Guidance; Health; Integrated Activities; Interpersonal Relationship; Job Skills; Kindergarten; Language Arts; Learning Activities; Mathematics Instruction; Occupational Information; Physical Education; Preschool Education; Responsibility; Role Perception; Science Instruction; Self Concept; Social Cognition; Social Studies; State Curriculum Guides; Life Planning; Life Events -- Missouri; Guides, Classroom -- Teacher